Guidance and Counseling in Islamic Perspective - Junaedi, Dedi; Sahliah, Sahliah; Hajar, Siti; Hermansyah, Hermansyah (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
This research discusses the development of a Guidance and Counseling model based on an Islamic perspective that is relevant to the needs of Indonesian society. The main problem is the dominance of Western psychological approaches in counseling services in Indonesia, which often ignore the spiritual dimension, even though the majority of Indonesian society is religious. This research aims to integrate Islamic values into Guidance and Counseling practices in order to improve individual psychological and spiritual well-being. The research method involves literature analysis and case studies at the IKIP Siliwangi Cimahi campus. This approach emphasizes the integration of Al-Qur'an and Hadith values in the counseling process, such as the use of prayer, dhikr, and advice based on Islamic teachings. The research results show that the Islamic Guidance and Counseling model is able to provide holistic solutions, including psychological and spiritual aspects, and is more relevant to Indonesian culture. This model increases the effectiveness of Guidance and Counseling services in helping individuals overcome problems, develop personal potential, and achieve prosperity in the world and the hereafter.